Using Mac OS X Mavericks - Wilson, Kevin. (Apress : Imprint: Apress, 2014)
Learn to use your Mac the easy way: no jargon, just clear, concise and to the point. Using Mac OS Mavericks is your handy guide to using a computer running Mavericks, providing a quick resource for both the beginner and the enthusiast. Using Mac OS Mavericks is your handy guide to using a computer running Mavericks, providing a quick resource for both the beginner and the enthusiast. Step-by-step techniques supported by photography and screen prints, and easy to follow text, make using a Mac a cinch. Whether you have just bought your first Mac, switched from Windows, or are a keen computer user, this lean reference will provide you with the underpinnings needed to use a Mac like a pro.